2023
DOI: 10.1029/2022gl102341
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Rings and Gravity Waves: Insights Into the Giant Eruption Plume From Tonga's Hunga Volcano on 15 January 2022

Abstract: This event continues to push the boundaries of our understanding of how explosive volcanism impacts the broader Earth system. In addition to significant local impacts on the Kingdom of Tonga (Purkis et al., 2023), the eruption created global-scale acoustic waves (Matoza et al., 2022), tsunamis (Omira et al., 2022), ionospheric and geomagnetic disturbances

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…data (Matoza et al, 2022) and tsunami runup measurements in the Tonga Archipelago (Purkis et al, 2023) also indicate an explosive event at that emission time. In addition, Van Eaton et al (2023) found a sudden increase in the plume's width at 04:07 UTC using GOES-17 full disk visible images. This minor anomaly is followed by two larger anomalies at 05:00 UTC (∼0.8 hPa, emission time 04:15 UTC) and 05:07 UTC (∼2.1 hPa, emission time 04:22 UTC).…”
Section: The Surface Pressure Waveformmentioning
confidence: 93%
“…data (Matoza et al, 2022) and tsunami runup measurements in the Tonga Archipelago (Purkis et al, 2023) also indicate an explosive event at that emission time. In addition, Van Eaton et al (2023) found a sudden increase in the plume's width at 04:07 UTC using GOES-17 full disk visible images. This minor anomaly is followed by two larger anomalies at 05:00 UTC (∼0.8 hPa, emission time 04:15 UTC) and 05:07 UTC (∼2.1 hPa, emission time 04:22 UTC).…”
Section: The Surface Pressure Waveformmentioning
confidence: 93%
“…After securing the plate to the impulse platform using a screw stand, the electrode and sample are enclosed in an acrylic box (secured by a Velcro strap) surrounding the electrode to contain post‐experimental material. Since peak values of thunderstorm cloud‐to‐ground lightning average 30 kA (Rakov & Uman, 2003) and volcanic lightning discharge ranges between ∼2 kA and hundreds of kA (Aizawa et al., 2016; Haney et al., 2018; Van Eaton et al., 2020, 2023), but is typically on the lower end of this range, the mineral powders were subjected to peak impulse currents of ∼25 and ∼40 kA. The current waveforms were recorded by a Tektronix TDS7104 1 GHz bandwidth digital oscilloscope at a sampling interval of 2 ns.…”
Section: Methodsmentioning
confidence: 99%
“…• A sufficiently powerful volcanic plume can create conditions conductive to electrical activity (Van Eaton et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…It was analyzed that the intense lightning activity during the eruption of Hunga Volcano in Tonga in January 2022, attributing it to the exceptional mass eruption rate that rapidly expanded and entrained abundant seawater, leading to its vaporization through magma-water interaction. The findings show that a sufficiently powerful volcanic plume can create the conditions for electrical activity (Van Eaton et al, 2023). (Latham & Williams, 2001) reported that the efficiency of lightning fires is less than 0.04 fires per cloud-to-ground flash or approximately one to four flashes in 100 starting fires in much of North America.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation